Entrevista a Elizabeth Mertz, autora de El lenguaje de la Facultad de Derecho : aprendiendo a pensar como un abogado - Pezzetta, Silvina (2013)
"The postdoctoral stay took place in October 2010 and was made possible thanks to a partial scholarship awarded by the University of Buenos Aires." -- The present interview to Prof. Elizabeth Mertz was conducted in Wisconsin during a short post-doctoral visit there. Prof. Mertz teaches at Wisconsin. She has a Ph.D. in Anthropology as well and she wrote the book The language of the Law School. Learning to think like a lawyer. The book is the result of the research she carried out on eight Law Schools in the USA using the theoretical tools provided by anthropology, with an especial focus on Michael Silverstein's ideas. The main focus was the study of the language since anthropology assumes that the way we speak has strong effects on the way we think and act. The methodology was qualitative and quantitative and included observation, focus groups and interviews. During the interview Prof. Mertz explained her theoretical worries, the relation between language's studies and law and the main results of her research.